Persistence of type 5 adenovirus DNA in cells transformed by temperature-sensitive mutant, H5ts125. - Mayer, A J (1977)
The characteristic of H5ts125, a temperature-sensitive DNA-minus mutant, to transform 3 to 8 times more rat embryo cells than wild-type 5 adenovirus was correlated with the persistence of an increased proportion of the viral genome in cells independently transformed at the nonpermissive (39.5 degrees) or semipermissive (36 degrees) temperature. Reassociation kinetics of the hybridization of 32P-labeled,HindIII restriction fragments of the viral genome and excess unlabeled, transformed cell DNA was used to measure the quantity of the viral genome in transformed cells. Three of four cell lines independently transformed and maintained at 36 degrees contained all regions of the viral genome; one line transformed at 39.5 degrees contained multiple copies representing all of the viral DNA; and one line contained a large proportion of the viral genome. The cell line transformed and maintained at 32 degrees contained a quantity of viral genome consistent with that usually found in cells transformed by wild-type 5 adenovirus.